„Kwazar”, „Fantom”, „Czerwony Karzeł”, „Inne Planety”. Kilka uwag krytycznych o nietypowej sytuacji fantastycznych fanzinów w kulturze polskiej - Kochanowicz, Rafał (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
In Poland, research-related fanzines rarely include writings edited by Polish fans of science fiction, horror and fantasy. Active fans edited amateur magazines which were very important because they popularized fantastic literature and culture in Poland. The role of fantastic fanzines was not limited solely to the promotion of amateur creativity or publishing translations of foreign fiction not available on the market, but also consisted in the creation of creative bonds between writers and readers. The remnants of the activities of Polish fantastic fiction fans are about one hundred titles including “Quasar”, “Red Dwarf” and “Other Planets”. These three fanzines as effects of pure amateur work are also very similar to the professional magazines. Each of them has a different poetics and thematic dominant. They have also published stories written by famous Polish writers such as Ewa Białołęcka and Andrzej Sapkowski.